PARADIGMA INSTRUMENTAL DALAM MANAJEMEN STRATEGIS: ANALISIS KRITIS ATAS PERSPEKTIF ETIKA FRED R. DAVID - Badri; Yulianti Caesaria; Eliyanti Mokodompit (Berajah Journal, 2026)
This article discusses the shift in strategic management paradigms that position business ethics, corporate social responsibility (CSR), and environmental sustainability no longer as operational constraints but as internal determinants of strategy quality. This study aims to critically evaluate Fred R. David's contribution in establishing the relationship between profit-seeking and planetary responsibility through the principle of good ethics is good business. This article uses a Critical Literature Review approach with a conceptual analysis of strategic management literature, specifically Chapter 10 of Strategic Management: Concepts and Cases. The results of the study indicate that business ethics, CSR, and sustainability in David's framework function as sources of social legitimacy, reputation, stakeholder trust, and long-term competitive advantage. Practices such as sustainability reporting and ISO 14000/14001 are understood as strategic instruments to strengthen environmental accountability. However, this article finds that David's model remains instrumental because ethics is primarily justified to the extent that it supports business performance. This model is also inadequate in addressing the risks of greenwashing and the complexities of developing countries. The implication is that managers need to gradually adopt ethical strategic management through a transparent organizational culture.